Radiation‐driven rotational motion of nanoparticles. (25th April 2018) - Liang, Mengning; Harder, Ross; Robinson, Ian
Abstract : The observation of the effects of radiation pressure of a Gaussian beam by tracking the rotation motion of single‐crystal nanoparticles is presented. Abstract : Focused synchrotron beams can influence a studied sample via heating, or radiation pressure effects due to intensity gradients. The high angular sensitivity of rotational X‐ray tracking of crystalline particles via their Bragg reflections can detect extremely small forces such as those caused by field gradients. By tracking the rotational motion of single‐crystal nanoparticles embedded in a viscous or viscoelastic medium, the effects of heating in a uniform gradient beam and radiation pressure in a Gaussian profile beam were observed. Changes in viscosity due to X‐ray heating were measured for 42 µm crystals in glycerol, and angular velocities of 10 −6  rad s −1 due to torques of 10 −24  N m were measured for 340 nm crystals in a colloidal gel matrix. These results show the ability to quantify small forces using rotation motion of tracer particles.